2011
DOI: 10.1371/journal.pone.0024040
|View full text |Cite
|
Sign up to set email alerts
|

Laforin, a Dual Specificity Phosphatase Involved in Lafora Disease, Is Present Mainly as Monomeric Form with Full Phosphatase Activity

Abstract: Lafora Disease (LD) is a fatal neurodegenerative epileptic disorder that presents as a neurological deterioration with the accumulation of insoluble, intracellular, hyperphosphorylated carbohydrates called Lafora bodies (LBs). LD is caused by mutations in either the gene encoding laforin or malin. Laforin contains a dual specificity phosphatase domain and a carbohydrate-binding module, and is a member of the recently described family of glucan phosphatases. In the current study, we investigated the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…3, A and B). This supports previous findings by Liu et al (45) and contradicts a recent report that laforin is monomeric based solely on size exclusion chromatography (44). Our structural analysis reveals that the laforin quaternary structure is stabilized by dimerization of its N-terminal CBM (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…3, A and B). This supports previous findings by Liu et al (45) and contradicts a recent report that laforin is monomeric based solely on size exclusion chromatography (44). Our structural analysis reveals that the laforin quaternary structure is stabilized by dimerization of its N-terminal CBM (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The physical and functional role of laforin oligomerization has been controversial (Dukhande et al, 2011; Koksal and Cingolani, 2011; Liu et al, 2006; Liu et al, 2009; Sanchez-Martin et al, 2013). In situ and in vivo experiments have demonstrated that laforin is able to both dimerize and multimerize, but different models have been proposed for the extent to which oligomers form and which domains contribute.…”
Section: Resultsmentioning
confidence: 99%
“…Glucan binding assays were performed as previously described with the following modifications (Gentry et al, 2007;Dukhande et al, 2011). All proteins used in the glucan binding assays were purified as described above without cleavage of the His 6 tag to maintain the epitope for immunoblot analysis.…”
Section: Glucan Binding Assaymentioning
confidence: 99%